Razmerje med neposrednimi zahtevki podizvajalcev in neposrednimi plačili podizvajalcem - Hrastnik, Blaž (Pravnik, 2014)
The article includes legal analysis of the relationship between the direct subcontractor claims as a rule of the law of obligations and direct payments to subcontractors as a part of public procurement rules. The article primarily defines both sets of rules and defines their legal nature (direct subcontractor claims as a cessio legis and direct payments to subcontractors as a part of assignment of receivables). In the main part of the article, the author critically examines the legal relationship based upon the regulation in the Slovenian law. He emphasises that the relationship, although important, is completely unregulated and that causes significant uncertainness in legal relationships. It is in particular stressed that both sets of rules can be regarded either as complementary or as exclusive. Following that, the author regards direct payments to subcontractors as lex specialis in respect to the direct subcontractor claims and therefore excludes its use; provided that the current Slovenian legislation may also support the opposite interpretation and that reveals that the current regulation does not deliver the necessary legal certainty.
Keywords: javna naročila; obligacije; podizvajalske pogodbe; pogodbe